2022
DOI: 10.1177/10600280221131396
|View full text |Cite
|
Sign up to set email alerts
|

Nivolumab/Relatlimab: A Novel Addition to Immune Checkpoint Inhibitor Therapy in Unresectable or Metastatic Melanoma

Abstract: Objective: The aim of this article is to assess available data regarding use of nivolumab/relatlimab for adult and pediatric patients 12 years of age and older with unresectable or metastatic melanoma. Data Sources: A search of PubMed conducted from August 2019 to August 2022 with the search terms Opdualag, nivolumab AND relatlimab, and BMS-986016 resulted in 14 publications. Study Selection and Data Extraction: Relevant clinical trials written in English language were analyzed. Data Synthesis: Nivolumab/relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Merck's LAG-3–targeting antibody favezelimab has already been tested in combination with pembrolizumab in a first-in-human study in advanced colorectal cancer with promising antitumor activity ( 46 ). In addition, a fixed-dose combination of the LAG-3 blocking antibody relatlimab and the PD-1 blocking antibody nivolumab, known as opdualag (Bristol Myers Squibb) approved by the FDA, has shown a promising improvement in PFS for patients with unresectable or metastatic melanoma ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Merck's LAG-3–targeting antibody favezelimab has already been tested in combination with pembrolizumab in a first-in-human study in advanced colorectal cancer with promising antitumor activity ( 46 ). In addition, a fixed-dose combination of the LAG-3 blocking antibody relatlimab and the PD-1 blocking antibody nivolumab, known as opdualag (Bristol Myers Squibb) approved by the FDA, has shown a promising improvement in PFS for patients with unresectable or metastatic melanoma ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…62 Bristol Myers Squibb's drug, Opdualag, the first fixeddose combination treatment of nivolumab and relatlimab, has recently received Food and Drug Administration approval for the first-line treatment of unresectable or advanced melanoma. 63 This coblockade of LAG-3 and PD-1 has demonstrated both safety and efficacy, offering superior benefits in terms of PFS compared with PD-1 blockade alone. 63 A phase II and III double-blind, randomized trial reported that combining the two ICs, LAG-3 and PD-1, demonstrated a more significant advantage in terms of 1-year PFS (47.7% vs. 36.0%) in comparison to anti-PD-1 monotherapy in patients with untreated metastatic or unresectable melanoma.…”
Section: Lymphocyte-activation Genementioning
confidence: 99%
“…63 This coblockade of LAG-3 and PD-1 has demonstrated both safety and efficacy, offering superior benefits in terms of PFS compared with PD-1 blockade alone. 63 A phase II and III double-blind, randomized trial reported that combining the two ICs, LAG-3 and PD-1, demonstrated a more significant advantage in terms of 1-year PFS (47.7% vs. 36.0%) in comparison to anti-PD-1 monotherapy in patients with untreated metastatic or unresectable melanoma. 64 Importantly, in the group receiving relatlimab-nivolumab, 18.9% of patients experienced treatment-related adverse events (grade 3 or 4), while for the nivolumab group, this percentage was lower (9.7%).…”
Section: Lymphocyte-activation Genementioning
confidence: 99%
See 1 more Smart Citation
“…13 The expression of LAG-3 may be observed on the cellular membrane of several immune cells, such as CD4 + , CD8 + , natural killer cells, and regulatory T cells. 14,15 LAG-3 cell surface receptor is induced on effector T lymphocytes in response to antigenic stimulation and its expression is maintained at high levels on CD4 + and CD8 + T lymphocytes in response to persistent antigen stimulation, being upregulated in melanoma. 4,16 The classic ligands of LAG-3 are major histocompatibility complex class II molecules, which are abundantly expressed in cutaneous melanomas.…”
Section: Mechanism Of Actionmentioning
confidence: 99%